2002
DOI: 10.1053/eujp.2001.0305
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive behaviour induced by dental application of irritants to rat incisors: A new model for tooth inflammatory pain

Abstract: Animal models simulating acute human pulpitis are still lacking. The rat incisors present a particular situation where most of their innervation is considered to be unmyelinated and concentrated mainly in the tooth pulp. This study reports on a new model for dental pain induced by inflammatory agents applied to the tooth pulps of incisors. In different groups of rats, artificial crowns were fixed on the lower incisors, after cutting 1-2mm of their distal extremities. A volume of 7-10 microl of solutions of sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 46 publications
0
32
0
3
Order By: Relevance
“…Thus, capsaicin, which specifically targets TRPV1, can stimulate CGRP release from isolated dental pulp (Gibbs and Hargreaves, 2008;Fehrenbacher et al, 2009), and transdentinal application of capsaicin to incisor dental pulp can evoke nocifensive behavior in rats (Chidiac et al, 2002). Finally, electrophysiological studies have identified capsaicin-sensitive fibers in dental pulp (Ikeda et al, 1997;Chaudhary et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, capsaicin, which specifically targets TRPV1, can stimulate CGRP release from isolated dental pulp (Gibbs and Hargreaves, 2008;Fehrenbacher et al, 2009), and transdentinal application of capsaicin to incisor dental pulp can evoke nocifensive behavior in rats (Chidiac et al, 2002). Finally, electrophysiological studies have identified capsaicin-sensitive fibers in dental pulp (Ikeda et al, 1997;Chaudhary et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Intradental perfusion of capsaicin is a newly developed model used to evaluate the pulpal response to noxious stimuli (31,32). It has also been applied to the cornea of the eye with measurement of TRPV1-mediated nocifensive behavior (33).…”
Section: Dental Injury Modelmentioning
confidence: 99%
“…The electromyographic activity method (Sunakawa et al, 1999) typically requires that the animal be unconscious, although one study utilized freely moving rats (Boucher et al, 1993). Most behavioral models used to date had a limited daily window of nociception recording, i.e., from min to hrs per day, with the nocturnal rats being placed in a test chamber during the light phase, which can cause stress in the animal (Chattipakorn et al, 2002;Chidiac et al, 2002;Chudler and Byers, 2005). In both conscious humans and rats, bite force has been used as a reliable measure for tooth pain and nociception, but the rat model requires training and/or restraint (A Khan et al, 2007a,b;J Khan et al, 2008).…”
mentioning
confidence: 99%
“…Several models have been used to investigate pulp pain, including: biting duration (Foong et al, 1982); bite force (Khan et al, 2008); dental injury and weight loss (Byers and Närhi, 1999); jaw-opening reflex (Rajaona et al, 1986); jaw electromyographic activity (Sunakawa et al, 1999); tongue protrusion directed to the injured tooth (Chattipakorn et al, 2002); behavioral changes in abnormal head movement, shaking of lower jaw, and rubbing of the mouth (Chidiac et al, 2002); exploring, freezing, and yawning (Chudler and Byers, 2005); and indirect measures of nociception with Von Frey filaments or heat (Le Bars et al, 2001). …”
mentioning
confidence: 99%